2011
DOI: 10.4103/0974-1216.85283
|View full text |Cite
|
Sign up to set email alerts
|

Laparoscopic myomectomy with aquadissection and barbed sutures

Abstract: The objective of this study was to evaluate the efficacy of aquadissection technique to reduce the blood loss in myomectomy and to assess the benefits and feasibility of the use of barbed suture for myometrial defect closure. Vasopressin is diluted with saline as 10 units of vasopressin for every 100 ml of saline. For a fibroid of about 8 cm size, 40 units of vasopressin is diluted in 400 ml of normal saline. The whole of 400 ml of this saline is injected in the myometrium. Incision is made on the uterus with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
2
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 8 publications
2
2
0
Order By: Relevance
“…However, the use of BS in laparoscopic myomectomy can reportedly alleviate inflammation and ensure even distribution of tension at the incision site, consequently reducing the likelihood of tissue ischemia, enhancing the healing process, and preserving ovarian function. 34,35 Consistent with the study by Chang et al, 36 both groups in our current study showed non-significantly higher AMH levels at 12 months compared with 3 months after surgery. This trend suggests that ovarian function can recover after surgery, which may be attributed to a compensatory mechanism of follicles (i.e.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…However, the use of BS in laparoscopic myomectomy can reportedly alleviate inflammation and ensure even distribution of tension at the incision site, consequently reducing the likelihood of tissue ischemia, enhancing the healing process, and preserving ovarian function. 34,35 Consistent with the study by Chang et al, 36 both groups in our current study showed non-significantly higher AMH levels at 12 months compared with 3 months after surgery. This trend suggests that ovarian function can recover after surgery, which may be attributed to a compensatory mechanism of follicles (i.e.…”
Section: Discussionsupporting
confidence: 92%
“…In agreement with our study, Usama et al 33 suggested that serum AMH levels declined by 18.32% in the BS group and 22.84% in the CS group at 3 months after traditional laparoscopic resection of ovarian endometrioma, with no difference in the degree of AMH decrease observed between groups. However, the use of BS in laparoscopic myomectomy can reportedly alleviate inflammation and ensure even distribution of tension at the incision site, consequently reducing the likelihood of tissue ischemia, enhancing the healing process, and preserving ovarian function 34,35 …”
Section: Discussionmentioning
confidence: 99%
“…No hemorrhagic complication occurred in any patient during surgery or postoperatively. 8 In present study 6% patient had intra-operative blood loss about 50 ml. Three patients received blood transfusion.…”
Section: Discussionsupporting
confidence: 44%
“…Guideline was 10 units for 100 ml of normal saline. 8 Now depending on number and size of fi broids diluted preparation was injected. Solution was injected around the periphery of the fi broid.…”
Section: Introductionmentioning
confidence: 99%